2013
DOI: 10.1002/adma.201302810
|View full text |Cite
|
Sign up to set email alerts
|

3D Graphene Oxide–Polymer Hydrogel: Near‐Infrared Light‐Triggered Active Scaffold for Reversible Cell Capture and On‐Demand Release

Abstract: An active cell scaffold based on a graphene-polymer hydrogel has been successfully fabricated. The macroporous hydrogel can efficiently capture cells not only through the bioadhesive ligand RGD but also through on-demand release of cells with an NIR light stimulus. The latter process shows better dynamic control over cells than traditional passive-hydrogel-based cell depots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
175
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(176 citation statements)
references
References 47 publications
1
175
0
Order By: Relevance
“…With regard to the reversible exchange of biochemical ligands, these dynamic chemistries are especially important for assays that require the capture and release of cells 148150 . Many existing substrates are degraded on release, but reversible technologies will enable these platforms to be used over multiple cycles, thereby enhancing their efficiency and cost-effectiveness for cellular 151154 and protein 155 screening. Finally, hydrogels with reversible changes in mechanics are needed to study how cells process stiffness signals over time, especially cells involved in fibrotic disease 156 as well as stem cells 122,126 .…”
Section: Looking Forwardmentioning
confidence: 99%
“…With regard to the reversible exchange of biochemical ligands, these dynamic chemistries are especially important for assays that require the capture and release of cells 148150 . Many existing substrates are degraded on release, but reversible technologies will enable these platforms to be used over multiple cycles, thereby enhancing their efficiency and cost-effectiveness for cellular 151154 and protein 155 screening. Finally, hydrogels with reversible changes in mechanics are needed to study how cells process stiffness signals over time, especially cells involved in fibrotic disease 156 as well as stem cells 122,126 .…”
Section: Looking Forwardmentioning
confidence: 99%
“…Despite the excellent prospects, G-gel still lacks superior chemical activity due to the deficiency of functional sites, which is not beneficial for its versatile application, typically the water purification [6][7][8][9][10][11]. It has been reported that the crosslinking of polymer with graphene produced functionalized G-gel, which is superior for water purification, such as poly(vinyl alcohol)/G-gel and poly(dopamine)/G-gel [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…Among the numerous applications of GO, biomedical applications such as drug delivery [8], photothermal therapy [9], cell scaffold [10], biomolecule detection [11][12][13] and molecular catalysis [14,15] have been under active development for a decade. The newly established systems are aimed to make the impossible assays possible or overcome the disadvantages of conventional analytical methods.…”
Section: Introductionmentioning
confidence: 99%